Life’s Crucial 9 Score as a Novel Role for Chronic Obstructive Pulmonary Disease Screening - Li W; Wen Y; Fan Y; Hu Z; Deng Z; Huang Q (International Journal of COPD)
Wenqiang Li,1,* Youli Wen,1,* Yuting Fan,2 Zefu Hu,3 Zhiping Deng,1 Qian Huang3 1Department of Respiratory and Critical Care Medicine, Zigong First People’s Hospital, Zigong, Sichuan Province, 643000, People’s Republic of China; 2Department of Clinical Medicine, North Sichuan Medical College, Nanchong, Sichuan Province, 637000, People’s Republic of China; 3Department of Respiratory and Critical Care Medicine, Dazhou Dachuan District People’s Hospital (Dazhou Third People’s Hospital), Dazhou, Sichuan Province, 635000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qian Huang, Department of Respiratory and Critical Care Medicine, Dazhou Dachuan District People’s Hospital (Dazhou Third People’s Hospital), Dazhou, 635000, Sichuan Province, People’s Republic of China, Tel +8615196767955, Email hq15196767955@163.com Zhiping Deng, Department of Respiratory and Critical Care Medicine, Zigong First People’s Hospital, Zigong, 643000, Sichuan Province, People’s Republic of China, Tel +8613608158051, Email zgsdzp1016@163.comPurpose: This study aims to investigate the association between the Life’s Crucial 9 (LC9) score and chronic obstructive pulmonary disease (COPD) in middle-aged and older adults.Patients and Methods: We screened the NHANES database for data from 2007– 2018. Logistic regression analysis and subgroup analysis were used to explore the association between LC9 score and COPD in middle-aged and older adults. Additionally, restricted cubic spline (RCS) was plotted to visually depict the dose-response relationship between the two.Results: A total of 12,030 participants were included, of whom 815 had COPD. After multivariate adjustment, the LC9 score was found to be inversely associated with COPD diagnosis. The RCS visually demonstrated a linear decreasing relationship between the two. Furthermore, subgroup analysis revealed no significant interaction across different subgroups, except for education level.Conclusion: The LC9 score is linearly and inversely associated with COPD diagnosis. Higher LC9 scores are associated with a lower COPD diagnosis in individuals aged 40 and above.Keywords: COPD, middle-aged and older adults, life’s crucial 9, diagnosis, cardiovascular health